Strategi Komunikasi Krisis Pemkab Badung dalam Penanganan Banjir di Badung, Bali - Mila Suhari; Dian Purworini (Universitas Medan Area, 2026)
This study aims to analyze the crisis communication strategies of the Badung Regency Government in handling floods as reported on Detik.com. This review is important because it quantitatively measures the dominance of government crisis communication strategies in a national online media outlet by categorizing news content into SCCT coding sheets. The method used is a descriptive quantitative approach through content analysis. The population comprises 40 news articles reporting the Badung Regency Government’s response to the Bali floods for the period 9 September to 30 October 2025. The sample was selected using purposive sampling. Results show that the most dominant strategies are Justification (37.5%), Compensation (27.5%), Excuse (10%), Apology (10%), Victimage (7.5%), Denial (5%), and Reminder (2.5%). Based on the Chi‑Square test, there is a significant difference in the distribution of strategies, indicating a strong dominance of the Justification approach. The study concludes that the Badung Regency Government adopts an explanatory and accommodative crisis communication pattern, characterized by the dominance of justification and compensation strategies; to enhance effectiveness and protect reputation, it is recommended that the Badung Regency Government combine justificatory narratives with concrete evidence of action.